COVID-19 Awareness System Based on Risk Assessment (COVID-19 Handling Implementation in Universitas Pekalongan): Sistem Kewaspadaan COVID-19 Berbasis Penilaian Risiko (Implementasi Penanganan COVID-19 di Universitas Pekalongan) - Yuniarti,; Ristiawati,; Nur Susanti, (Media Kesehatan Masyarakat Indonesia, 2021)
World Health Organization (WHO) announced COVID-19 as a global pandemic since it occurred massively in the whole part of the world. COVID-19 has an impact on life’s aspects, including the academic life aspect. This study aims to assess the risk factors of COVID-19 to build an awareness system of COVID-19 in higher education. This research is qualitative research with a case study approach regarding the risks of COVID-19 at Universitas Pekalongan. Variables were including risk identification, risk analysis, and risk evaluation. Information about the data source, including a university leader, and its vice, acts as a primary informant, the leader of units, and faculty acts as a triangulation informant. Structured-interview was applied to analyze risk identification, and risk analysis, compared criteria and risk impact analyzed the risk of evaluation. This study was conducted from June to August 2020 and held in Universitas Pekalongan. From risk identification and risk analyze there are six results: transmission of COVID-19 with a score of 25, Tri Dharma Perguruan Tinggi’s activities are not being optimally organized (score of 6), learning competence has not achieved a score of 9, decreased income (score 12), difficulty adapting in mastering internet-based technology (score of 4) and decreased number of new students (score of 12). Refers to risk evaluation risk known that transmission of COVID-19 is the highest-level risk. Risk assessment of COVID-19 impact is developing in the awareness system for comprehensive protection and it’s a reference for re-engineering the change strategy in higher education affected by COVID-19.